2003
DOI: 10.1007/s00122-002-1187-7
|View full text |Cite
|
Sign up to set email alerts
|

Powdery mildew resistance gene Pm22 in cultivar Virest is a member of the complex Pm1 locus in common wheat (Triticum aestivum L. em Thell.)

Abstract: The powdery mildew resistance gene Pm22, identified in the Italian wheat cultivar Virest and originally assigned to wheat chromosome 1D, was mapped to chromosome 7A with the aid of molecular markers. Mapping of common AFLP and SSR markers in two wheat crosses segregating for Pm22 and Pm1c, respectively, indicated that Pm22 is a member of the complex Pm1 locus. Pm22 also showed a pattern of resistance reaction to a differential set of Blumeria graminis f. sp. tritici isolates that was distinguishable from those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(41 citation statements)
references
References 34 publications
3
38
0
Order By: Relevance
“…On chromosome 7A, as discussed previously, one of the QTL detected in the RIL population could correspond to the QTL detected near the marker Xgwm344 in the F 2:3 mapping population by Chantret et al (2001). Two alleles of Pm1, namely Pm1c and Pm1e, have been mapped near this marker by Singrün et al (2003), while two powdery mildew resistance genes from einkorn (Triticum monococcum) have also been mapped in this region (Yao et al 2007). …”
Section: Marker Order and Map Coveragesupporting
confidence: 54%
“…On chromosome 7A, as discussed previously, one of the QTL detected in the RIL population could correspond to the QTL detected near the marker Xgwm344 in the F 2:3 mapping population by Chantret et al (2001). Two alleles of Pm1, namely Pm1c and Pm1e, have been mapped near this marker by Singrün et al (2003), while two powdery mildew resistance genes from einkorn (Triticum monococcum) have also been mapped in this region (Yao et al 2007). …”
Section: Marker Order and Map Coveragesupporting
confidence: 54%
“…Clusters of genes conferring resistance to wheat diseases on wheat chromosomes are not randomly distributed ). Genes within a cluster can be allelic or closely linked, for example, the powdery mildew resistance genes at the Pm1 (Singrün et al 2003) and Pm3 loci (Srichumpa et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Breeding for resistance is the most profitable and environmentally acceptable strategy to control powdery mildew. More than 60 powdery mildew resistance genes located at 41 loci (Pm1-Pm45, Pm18 = Pm1c, Pm22 = Pm1e, Pm23 = Pm4c, Pm31 = Pm21) (Ma et al 2011;Hsam et al 1998;Singrün et al 2003;Hao et al 2008;Xie et al 2011) have been identified and designated in wheat and its wild relatives.…”
Section: Introductionmentioning
confidence: 99%
“…To date, 32 major resistance genes to powdery mildew (Pm1-Pm32) have been reported in wheat (Hsam & Zeller, 2002;Hsam et al, 2003;Xie et al, 2003). However, due to allelism of Pm17, Pm18 and Pm22 to already documented genes, they map to 29 loci (Hsam & Zeller, 2002;Singrün et al, 2003). Very recently, Yahiaoui et al (2004) were the first to clone a powdery mildew resistance gene (Pm3b) from hexaploid wheat supported by the genome sequence information of wheat species with lower ploidy levels.…”
Section: Introductionmentioning
confidence: 95%
“…amplified fragment length polymorphism (AFLP; Vos et al, 1995), and Chinese Spring (CS) wheat -for which aneuploid stocks are available -as a parent in developing progeny used in bulked segregant analyis (Michelmore et al, 1991) has greatly expedited the mapping of resistance genes. Recently, the wheat powdery mildew resistance genes Pm24 (Huang et al, 2000b), Pm1e (Pm22) (Singrün et al, 2003) and mlRD30 (Singrün et al, 2004) were allocated to specific genomic regions by means of nullitetrasomic mapping of linked repulsion phase AFLP markers and chromosome-specific microsatellite typing. In the present study, we have used this strategy for the genetic and breakpoint interval (bin) mapping of a novel powdery mildew resistance gene from the T. dicoccoides-derived line Zecoi-1.…”
Section: Introductionmentioning
confidence: 99%